Independent primary cutaneous and mammary apocrine carcinomas with neuroendocrine differentiation: Report of a case and literature review. (2nd July 2021) - DeCoste, Ryan C.; Carter, Michael D.; Barnes, Penelope J.; Andea, Aleodor A.; Wang, Min; Rayson, Daniel; Walsh, Noreen M.
Abstract: Cutaneous apocrine carcinomas share common features with their counterparts in the breast; hence, metastatic mammary carcinoma must be excluded before such lesions can be designated primary cutaneous neoplasms. Primary tumors from either source rarely exhibit neuroendocrine differentiation. We report a case of a 72‐year‐old female with a painless 1.2‐cm scalp nodule. An incisional biopsy revealed dermal involvement by an invasive apocrine carcinoma juxtaposed to a benign apocrine cystic lesion. Immunohistochemically, the carcinoma expressed neuroendocrine proteins including synaptophysin, chromogranin, and CD56. A primary cutaneous apocrine carcinoma with neuroendocrine differentiation was favored, but additional investigations to exclude breast origin were recommended. These revealed a 1.1‐cm nodule in the right breast, which proved to be an invasive ductal carcinoma, morphologically and immunophenotypically similar to the scalp lesion. This confounded the case, yet factors militating against metastatic breast carcinoma to skin included (a) the small size of the mammary tumor, (b) absence of other metastatic disease, and (c) juxtaposition of the scalp carcinoma to a putative benign precursor. Molecular studies were undertaken to resolve the diagnostic quandary. Single nucleotide polymorphism microarray analysis revealed distinct patterns of chromosomal copy number alterations in the two tumors, supporting the concept of synchronous and unusual primary neoplasms.